The Nutraceutical Value of Foods and Its Health Benefits: A Review - Amanullah, Mohammad; Nahid, Meher; Hosen, SM Zahid; Akther, Shireen; Kauser-Ul-Alam, Md (Health Dynamics, 2024)
The increasing interest in nutraceuticals has spotlighted the potential of local foods as sources of health-promoting bioactive compounds. This narrative review explores the nutraceutical value of local foods, emphasizing the processing methods that enhance their health benefits. By examining a variety of indigenous food sources, we delve into the specific bioactive components they contain, such as polyphenols, flavonoids, vitamins, and minerals. Advanced processing techniques, including fermentation, encapsulation, and enzymatic treatments, are discussed for their roles in maximizing the bioavailability and efficacy of these compounds. Furthermore, the health impacts of these nutraceuticals are analyzed, focusing on their potential to prevent and manage chronic diseases such as diabetes, cardiovascular diseases, and cancer. This review underscores the importance of leveraging local biodiversity to develop sustainable and effective nutraceutical products, offering insights into future research directions and applications in the nutraceutical industry. By integrating traditional knowledge with modern processing technologies, the potential of local foods as nutraceuticals can be fully realized, contributing to both public health and local economies.